Availability of Laboratory Diagnosis of Gonorrhoea and Its Meaning in Case Reporting in Shandong Province, China - Chen X; Gan Y; Liu D (Dove Medical Press, 2023)
Xinlong Chen,1 Yanling Gan,2 Dianchang Liu2 1Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, 610072, People's Republic of China; 2Department of STI and Leprosy Prevention and Control, Shandong Provincial Hospital for Skin Diseases & Shandong Provincial Institute of Dermatology and Venereology, Shandong First Medical University & Shandong Academy of Medical Sciences, Jinan, Shandong, 250022, People's Republic of ChinaCorrespondence: Dianchang Liu, Tel +86 531-87298850, Email dianchangliu@163.comBackground: Gonorrhea, caused by the bacterium Neisseria gonorrhoeae (NG), is a major public health concern worldwide.Aim of the Study: The aim of this study is to understand the availability of laboratory diagnosis of gonorrhoea in Shandong province and its meaning in case reporting.Methods: Two surveys were conducted among hospitals providing clinical services for sexually transmitted infection (STI) in Shandong Province in 2012 and 2018. The availability of laboratory tests for NG and distribution of reported gonorrhea cases were compared among different hospitals provided clinical services for STI in Shandong province. Descriptive analysis and Chi-square were used for statistical analysis.Results: Smear, culture and PCR tests for NG were used among 301(74.69%), 123(30.52%), 43(10.67%) hospitals in 2012 and 356(74.48%), 176(36.82%) and 73(15.27%) hospitals in 2018, respectively. Significant differences were observed in the availability of smear among hospitals at different levels (X2=12.159, p=0.000) and with different affiliations (X2=4.551, p=0.033) in 2018. Significant differences were observed in the availability of culture and PCR tests among hospitals at different levels both in 2012 (X2=34.532, p=0.000; X2=7.380, p=0.007) and 2018 (X2=49.820, p=0.000; X2=21.658, p=0.000). The availability of culture and PCR tests for NG among hospitals in 2018 was higher than that in 2012 (X2=3.870, p=0.049; X2=4.050, p=0.044). More hospitals reported gonorrhea cases in 2018 than in 2012 (X2=6.768, p=0.009). A significant difference was observed in distribution of case reporting among hospitals at different levels in 2018 (X2=6.975, p=0.008) and among different types of hospital both in 2012 (X2=52.362, p=0.000) and 2018 (X2=74.478, p=0.000).Conclusion: Poor availability of NG laboratory tests affects case reporting, and which is a crucial reason leading to underreporting of gonorrhea cases in Shandong province.Keywords: gonorrhea, availability, laboratory tests, underreporting